MOTIVATION, ANXIETY AND GENDER: HOW THEY INFLUENCE THE ACQUISITION OF ENGLISH AS A SECOND LANGUAGE FOR SAUDI STUDENTS STUDYING IN IRELAND - Alhammad, Mohammad (PEOPLE: International Journal of Social Sciences, 2017)
Many students from Saudi Arabia go abroad to advance their studies for varied reasons. Ireland is a new experience for most of them. The aim of this study is to investigate how factors such as motivation and anxiety interact with gender issues to affect the acquisition of English as a second language for Saudi students choosing to study in Ireland. The research will investigate the role of motivation, anxiety and gender in the learning process for Saudi students studying English language schools in Ireland. A mixed methods approach will be used for the purposes of this research. In the case of this study, the sequential mixed design where the qualitative approach follows the quantitative will be applied. The data will be collected using questionnaires and follow up interviews. he questionnaire includes 30 multiple choice questions. The questionnaire will be made available online and participants will be given the option to volunteer for an interview by clicking an option and entering their contact details. The research subjects will be Saudi students at university language centers in Ireland.